Movement Patterns of Frugivorous Birds Promote Functional Connectivity among Chaco Serrano Woodland Fragments in Argentina. (16th June 2015) - Díaz Vélez, María Celeste; Silva, Wesley R.; Pizo, Marco A.; Galetto, Leonardo
Abstract Movement patterns of frugivorous birds may be altered in anthropogenically fragmented landscapes, with possible consequences for seed dispersal and plant recruitment. We studied the movement patterns and functional connectivity of six frugivorous bird species (Colaptes melanochloros, Thraupis bonariensis, Pitangus sulphuratus, Saltator aurantiirostris, Turdus amaurochalinus, and Elaenia spp.) in a fragmented Chaco‐woodland landscape in Argentina. We recorded the directions of bird movements (arrivals and departures) and whether their destination was oriented toward a specific neighboring fragment. We evaluated the movement rates, distance of interpatch movement, and functional connectivity within the landscape for the six bird species. We applied a novel approach, graph theory, to represent bird movement patterns in the landscape and the functional connections among fragments for each bird species. Bird movements were recorded at point‐count stations established along the edges of each fragment. The directions of arrival and departure movements from and to neighboring fragments revealed complex movement patterns. However, the destination of bird movements after leaving the focal fragments was usually concentrated on only a few neighboring fragments of different sizes. Pitangus sulphuratus and T. bonariensis showed larger movement rates and higher functional connectivity (number of graphs and functional area) than the other frugivorous species. The functional connectivity mediated by movement of frugivorous birds may promote seed dispersal of many bird‐dispersed plant species. As forest loss and fragmentation of Chaco subtropical forests increase, understanding the pivotal role of mobile links exerted by avian seed dispersers is vital to maintaining and conserving this unique ecosystem.